Quality improvement project for managing elevated blood pressure in a primary care setting - Thomas SM; Cassells HB (Dove Medical Press, 2017)
Stephanie M Thomas,1 Holly B Cassells2 1Vital Life Wellness Center, 2Ila Faye School of Nursing, University of the Incarnate Word, San Antonio, TX, USA Abstract: Elevated blood pressure (BP) and prehypertension increase the risk of cardiovascular diseases, a national health concern. This article presents a quality improvement project implemented within a primary care setting that aimed at lowering cardiovascular risk by improving the identification, treatment, and follow-up of patients with elevated BP. This project was designed and implemented to address the identified deficiencies contributing to poor identification and follow-up of patients with elevated BP. The intervention was multi-pronged and comprised a staff educational program, introduction of a new method for measuring BP using the BpTRU™ device, and patient educational intervention. A significant improvement in staff BP knowledge scores was achieved following the intervention (p<0.05). Patient participants also exhibited a significant improvement in post-intervention BP measurements (p<0.05). This project showed that the implementation of a quality improvement project in a primary care setting can lead to significant improvements in staff BP knowledge and patient BP readings. However, future research in this area is required to determine whether particular lifestyle changes are directly associated with the reduction in BP. Keywords: prehypertension, elevated blood pressure, BpTRU™, quality improvement